Equity and productivity assessments in the Olifants River Basin, South Africa - Prasad, Krishna Chandra; van Koppen, Barbara; Strzepek, K.M. (2006)
Emerging approaches to water resources development and management typically highlight equity and productivity as two main objectives. In the context of integrated water resources management within a river basin, managers and stakeholders often need a comparative assessment of different options for water augmentation and/or allocation. Pitting such options against predefined objectives, such as equity and productivity, requires an assessment of the effects that available options will have on these objectives. Available documentation indicates that not only does the interpretation of such objectives vary widely, but also the available methods for assessing equity and productivity run into significant limitations in the availability of adequate data. This limitation has largely kept decision makers from gaining a comprehensive overview of equity and productivity scenarios, whether within or across sectors, that could facilitate better-informed decisions. To address this methodological gap, this article scrutinizes different notions associated with equity and water productivity, and limitations in prevalent assessment methods with the view to develop and demonstrate pragmatic methodologies for assessing equity and productivity in data-scarce contexts. The discussion and findings are based on a review of relevant literature and empirical and consultative research work in the Olifants River basin in South Africa. The demonstrated methodologies for assessing equity and productivity, besides being useful in data-scarce contexts, are insightful for initiating several policy measures and also for exploring the relationship between equity and water productivity.